Learning in work: perceptions from working teenagers. Issue 4 (19th May 2018) - Simpson, Amanda; McKechnie, Jim; Hobbs, Sandy
ABSTRACT: Research within the United Kingdom has shown that it is common for school students to combine full-time education with part-time employment. Attention has tended to focus on the negative impact this may have with limited consideration to the potential benefits. Some studies have indicated that skill acquisition may be one such benefit, but studies typically pay little attention to the views of young employees and fail to explore potential variations in skill development between age groups and job sectors. This study addresses this gap. Younger (14 and 15 year olds) and older (16 to 18 years) school students working in the retail and catering industries participated (n = 35). Two interviews were carried out facilitated by workplace observation and on-the-job event recording. Results suggest that opportunities for acquiring skills are common for both younger and older workers in both retail and catering jobs. Differences in perceptions between age groups and job sectors were small with the exception of the areas of future learning and the types of skills. In addition, retail workers tend to see more opportunities for learning than those in catering. These results support those who see such employment as potentially valuable.